Case Report: Hip arthroplasty after fracture-related joint infection caused by extensively drug-resistant Klebsiella pneumoniae - Fischer, Maximilian; Nonnenmacher, Lars; Reichert, Johannes C.; Bohnert, Jürgen A.; Idelevich, Evgeny A.; Doğan, Eyüp; Becker, Karsten; Wassilew, Georgi I. (Frontiers in Surgery, 2024)
This case-report focuses on a 23-year-old soldier suffering from a fracture-related hip joint infection (FRI) due to extensively drug-resistant Klebsiella pneumoniae and Staphylococcus epidermidis. The patient underwent multiple septic revision surgeries including the removal of remaining shrapnel accompanied by last-resort antimicrobial therapy with cefiderocol and colistin. Additionally, the surgeries included repeated tissue sampling for microbiological and histopathological analysis.An antibiotic-loaded cemented filler containing cefiderocol was used to improve local antimicrobial therapy. The biopsies prior to and during hip replacement surgery confirmed successful microbe eradication.Hip arthroplasty restored hip joint function and significantly improved patient's quality of life.The utilization of a trabecular metal shell and a meta-diaphyseally anchored cementless hip stem ensured secure implant fixation and early patient mobilisation. An adjusted biofilm active oral antimicrobial therapy after arthroplasty intervention was continued to prevent early periprosthetic joint infection. This case emphasizes the difficulties of managing FRI and multidrug-resistant pathogens. It contributes valuable insight into navigating complex orthopedic cases while ensuring successful hip arthroplasty outcomes.In conclusion, early interdisciplinary collaboration, appropriate antimicrobial therapy along with tailored surgical interventions are crucial for managing such complex cases successfully.